COMPENSATION OF NON-PECUNIARY DAMAGE CAUSED BY UNLAWFUL OR UNJUSTIFIED RESTRICTION OF LIBERTY - Kaļva, Aldis (Administrative and Criminal Justice, 2018)
In this publication it was research non-pecuniary damages caused by law enforcement agency and its indemnification. As the goal of publication was set to discover and analyse the problem about non-pecuniary damages caused by law enforcement agency and its indemnification and to investigate whether the newly adopted law on Compensation for Damage Caused in Criminal Proceedings and Administrative violations eliminates pre-existing problems with indemnification of non-pecuniary damage caused by law enforcement agency. The raised aim was achieved. It was found, that law on Compensation for Damage Caused in Criminal Proceedings and Administrative Violations eliminates pre-existing problems when courts had problems determining the amount of compensation of non-pecuniary damages in accordance with Civil law article 5. However there are problems with fixed calculation of daily wages in the article 15. of the law on Compensation for Damage Caused in Criminal Proceedings and Administrative violations.The article uses the systemic, dogmatic and comparative method of studying and analyzing normative acts and court rulings.